2020
DOI: 10.3389/fevo.2019.00499
|View full text |Cite
|
Sign up to set email alerts
|

Sensing the Danger Signals: cis-Jasmone Reduces Aphid Performance on Potato and Modulates the Magnitude of Released Volatiles

Abstract: In response to herbivory, plants synthesize and release variable mixtures of herbivore-induced plant volatiles (HIPVs) as indirect defense traits. Such induction of indirect plant defense can also be "switched on" by certain chemicals known as priming agents. Preceding work showed that the plant HIPV cis-jasmone (CJ) induced the emission of aphid defense-related volatiles affecting their behavioral response. However, little is known about the extent to which CJ-induced volatiles impacts aphid performance. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 86 publications
(124 reference statements)
0
11
0
Order By: Relevance
“…A previous study has also shown that changes in the JA signaling pathway are associated with the inhibition of A. gossypii populations after caterpillar feeding 10 . Moreover, cis ‐jasmone induces plant resistance and inhibitory effects against aphid populations in the field 42–44 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A previous study has also shown that changes in the JA signaling pathway are associated with the inhibition of A. gossypii populations after caterpillar feeding 10 . Moreover, cis ‐jasmone induces plant resistance and inhibitory effects against aphid populations in the field 42–44 …”
Section: Discussionmentioning
confidence: 95%
“…10 Moreover, cisjasmone induces plant resistance and inhibitory effects against aphid populations in the field. [42][43][44] JAZ proteins interact with the JA signaling pathway and help plants respond to biological stress. [45][46][47][48] We found that several genes were in the JAZ protein synthesis were significantly increased, and that JA was significantly more abundant in plants fed upon by H. armigera than in those suffering from mechanical damage alone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from T. absoluta larvae, previous studies have shown the efficacy of ( Z )-jasmone against immature stages of other insect pests. For instance, Sobhy et al (2020) reported that priming potato plant with ( Z )-jasmone negatively impacts the performance traits of aphids Macrosiphum euphorbiae (Thomas) (Hemiptera: Aphididae). Similarly, Black et al (2003) reported the inhibitory effect of JA and this can be used as a vaccine against the leafminers (Diptera: Agromyzidae).…”
Section: Discussionmentioning
confidence: 99%
“…This compound can be found in Polygonum hydropiper [18], Satureja hortensis [19]. Jasmon has biological activity and can be used to decrease aphid growth and reproduction [20]. Meanwhile, austrobailignan has the potential for anticancer [21].…”
Section: Seed and Mace Chemical Compoundmentioning
confidence: 99%